Anak Menekuni Profesi yang Sama dengan Orang Tua: Suatu Studi Fenomenologi pada Keluarga Polisi - Gytha Larasati Jerry; Maihasni Maihasni; Alfan Miko (ARISTO, 2019)
This article is about intergenerational social mobility, that is about children achievement compare to that of their parent. One of aspects of intergenerational social mobility is occupation. Nowaday different oportunity of profession is open for children. However it is found that the is the reality whereby children pursuing the same profession as the profession of their parents. This article discusses about causes of children choosing the same profession with the profession of their parents. The children studied are those whose parents profession midle rank police officers.  Using qualitative research data with the case study method of 7 police children and by using phenomenological theory. The finding of  this research shows that the police children are motivated to choose police officer for their profession,because of having proud of police profession. This is because of unique experiences that children get when they observe their parents’ routine working activities. That parents’ working activity inspire them to pursue the same profession with their parents.